Analisis Kesulitan Belajar Matematika Materi Sistem Persamaan Linear Dua Variabel - AA Biban Azhimuh; Muhammad Turmuzi; Wahidaturrahmi Wahidaturrahmi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study was conducted to determine the degree of difficulty in learning mathematics in grade X students with the population in this study is 359 students grade X and the number of study samples is 72 students were taken with cluster sampling techniques. Data collection techniques in this study used a essay test and unstructured interview questions for 10 students. The instrument of this study are in the form of mathematical essay questions that are closed to the material system of linear equations in two variables for 4 problems. The data obtained were analyzed by fit student answers and key answers in learning difficultiy analysis guide. The results of this study indicate that students of class X in the academic year 2019/2020 had the most difficulty learning principle in the amount of 21.90% which is included in the low category level. While students who had difficulty learning concepts and operations are 13.90% and 12.34% respectively included in the very low category level.